Soil and tree species traits both shape soil microbial communities during early growth of Chinese subtropical forests. (May 2016) - Pei, Zhiqin; Eichenberg, David; Bruelheide, Helge; Kröber, Wenzel; Kühn, Peter; Li, Ying; von Oheimb, Goddert; Purschke, Oliver; Scholten, Thomas; Buscot, François; Gutknecht, Jessica L.M.
Abstract: A better understanding of the linkages between aboveground and belowground biotic communities is needed for more accurate predictions about how ecosystems may be altered by climate change, land management, or biodiversity loss. Soil microbes are strongly affected by multiple factors including local abiotic environmental conditions and plant characteristics. To find out how soil microbial communities respond to multiple facets of the local soil and plant environment, we analysed soil lipid profiles associated with three-year-old monocultures of 29 tree species. These species are native of the diverse subtropical forests of southeast China and greatly vary in functional traits, growth or biomass characteristics, and phylogenetic relatedness. Along with the traits of each tree species, we also determined the soil and plot characteristics in each monoculture plot and tested for phylogenetic signals in tree species-specific microbial indicators. Microbial community structure and biomass were influenced by both soil properties and plant functional traits, but were not related to the phylogenetic distances of tree species. Specifically, total microbial biomass, indicators for fungi, bacteria, and actinomycetes were positively correlated with soil pH, soil organic nitrogen, and soil moisture. Our results also indicate that leaf dry matter content and the leaf carbon to nitrogen ratio influence multivariate soil microbial community structure, and that these factors and tree growth traits (height, crown or basal diameter) positively promote the abundances of specific microbial functional groups. At the same time, a negative correlation between leaf nitrogen content and Gram positive bacterial abundance was detected, indicating plant–microbial competition for nitrogen in our system. In conclusion, even at early stages of tree growth, soil microbial community abundance and structure can be significantly influenced by plant traits, in combination with local soil characteristics. Highlights: Species identity, with soil properties, shape microbial communities even at early tree growth. Tree species traits explain less variation in microbial communities than soil characteristics. Tree species phylogeny itself does not drive microbial community development.